Implementation of Smart Box Media in Problem-Based Learning to Improve Students' Scientific Literacy on Environmental Pollution - Hesti Eka Nur Dianti; Indri Susanti; Kiki Septaria (Indonesian Journal of Mathematics and Natural Science Education, 2025)
This study aims to improve students' scientific literacy by applying the Problem-Based Learning (PBL) model assisted by smart box media on environmental pollution material. This study uses a pre-experimental method with a one-group pre-test post-test design and purposive sampling. The data analysis techniques applied in this study are hypothesis testing using paired sample t-test, n-gain test, and product moment correlation. The results showed that the implementation of learning was 89.67% which was included in the very good category, paired sample t-test was 0.000. And strengthened by the n-gain test of 0.59 with a moderate category and the correlation between student learning outcomes and scientific literacy showed a significance value of 0.420 in the moderate correlation category. The conclusion of this study is that the PBL model assisted by Smart Box media has an effect on students' scientific literacy which can increase significantly from their initial level, and there is a relationship between student learning outcomes using the PBL model assisted by smart box media and scientific literacy.